Microwave Absorption of Coconut Wasted Derived Activated Carbon - Soleimani, H. (Springer Science and Business Media B.V., 2021)
Recently, electromagnetic (EM) interference as an adverse effect of the proliferation of technologies utilizing EM waves has become a serious problem. EM wave absorbers have been extensively utilized as an effective means of eliminating EMI. Activated carbon derived from agricultural waste has been identified as potential material to fabricate an ideal EM wave absorber. This study investigates activated carbon prepared from coconut fiber as an EM wave absorber at X-band frequency. Coconut fiber Activated carbon at 600Â Â°C exhibited the highest surface area of 228.689Â m2/g and 5.9Â nm number of pores which is beneficial for microwave absorption. COMSOL Multiphysics software was used to simulate the EM scattering parameters of the coconut fiber activated carbon. A good microwave absorption performance was observed minimum reflection loss value of â41.78Â dB at 10.8Â GHz at a thickness of 4.0Â mm. This result shows that activated carbon prepared from coconut fiber can function as an EM wave absorber at X-band frequency. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.